CO-MORBIDITIES OF HIDRADENITIS SUPPURATIVA - Kirthi Jeyarajah, Shivashini (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
Hidradenitis suppurativa (HS), is a chronic inflammatory skin disorder which can have debilitating consequences if not managed appropriately from early on of its course of disease. Patients with this condition, also previously known as 'acne inversa' present with recurrent, inflamed nodules in intertriginous areas such as the axillary, inguinal, and perianal areas. In more severe stages, this condition can lead to the formation of fistulas, sinus tracts, and extensive scarring. Various pathogenic mechanisms have been proposed in HS, including immune dysregulation, smoking, obesity and genetics however, the precise etiology remains to be elucidated. There is some evidence in the literature demonstrating the association of HS with inflammatory bowel disease, cardiovascular disease risk factors, arthritis and psychiatric disorders, suggesting that HS is a systemic disease. In our thesis we specifically investigated two comorbidities, Cardiovascular risk and psychological impact of this condition.Our prospective case-controlled study demonstrated that patients with HS have a significantly increased cardiovascular disease risk. We also showed for the first time to our knowledge that patients with HS have a significantly higher relative QRISK2 which is a tool used to evaluate absolute and relative cardiovascular risk in patients.We also found an increased prevalence of hyperhomocysteinemia within the HS cohort, as a non-classical cardiovascular risk factor that can further increase their risk of cardiovascular disease. Furthermore, we demonstrated in this thesis that our very young cohort of HS patients tend to have a pro-atherogenic lipid profile with significantly higher numbers of small dense LDL and a non-Type A lipoprotein profile. In terms of HS and its level of impact on mental health within our patients, we found that HS imposes a significant impairment in quality of life on patients who have this condition, with different type of distress being exhibited by the HS group when compared to psoriasis patients.We also showed that patients with HS have significantly higher levels of depression and anxiety than patients with psoriasis. This condition understandably has been proven to have a severe, adverse impact on patient's physical, social and mental health wellbeing, therefore warranting a holistic management approach by treating physicians.
APPROVED
Keywords: Hidradenitis Suppurativa; Comorbidities; Cardiovascular disease; Lipoprotein analysis; Psychological Distress